Peningkatan Karakter dan Kemampuan Membaca Permulaan Melalui Metode Permainan Kartu Bergambar pada Siswa Kelas II SDI Bontoloe Kecamatan Bontolempangan Kabupaten Gowa - Abrina Maulidnawati Jumrah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this research was to determine the character building and the reading ability of the second-grade students of SDI Bontoloe. The type of this research is Classroom Action Research (CAR) which consists of 4 stages, namely planning, implementation, observation and reflection. This research was conducted at SDI Inpres Bontoloe in the odd semester of academic year 2020/2021. The subjects of this research were teachers and the second-grade students of SDI Bontoloe. The sample of this research is 17 students. The research instrument is observation, learning outcomes test and documentation. The data analysis technique is the analysis of teacher teaching and student learning activities, students’ character and students’ reading ability analysis. From the results of student learning activities in cycle I and cycle II, it can be concluded that there was an increase of reading ability of the second-grade students of SDI Bontoloe from 52.09% to 88.22%. Likewise, students’ learning outcomes have increased. It shows that there was an increase at students’ learning activities in reading ability through the use of picture card game method.